2016
DOI: 10.1007/s10616-016-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Native matrix-based human lung alveolar tissue model in vitro: studies of the reparatory actions of mesenchymal stem cells

Abstract: Studies of lung diseases in vitro often rely on flat, plastic-based monocultures, due to short lifespan of primary cells, complicated anatomy, lack of explants, etc. We hereby present a native 3D model with cues for repopulating epithelial cells. Abilities of mesenchymal stem cells (MSC) to modulate bacterial lipopolysaccharide (LPS) and cigarette smoke-induced injury to pulmonary epithelium were tested in our model. Post-mortem human lung tissue was sliced, cut and decellularized. Resulting matrix pads were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…This indicates local volume-weighted hydrodynamic stresses ( τ nt = 4.96 × 10 −3 Pa, τ nn = 1.15 × 10 −3 Pa, Jossen et al [ 1 ]) acting on the MC-cell-aggregates controlled their size to some extent. This observation also agreed well with literature findings [ 40 , 41 ]. Furthermore, the results indicated that increased MC-cell-aggregation mainly took place during the stationary growth phase.…”
Section: Resultssupporting
confidence: 94%
“…This indicates local volume-weighted hydrodynamic stresses ( τ nt = 4.96 × 10 −3 Pa, τ nn = 1.15 × 10 −3 Pa, Jossen et al [ 1 ]) acting on the MC-cell-aggregates controlled their size to some extent. This observation also agreed well with literature findings [ 40 , 41 ]. Furthermore, the results indicated that increased MC-cell-aggregation mainly took place during the stationary growth phase.…”
Section: Resultssupporting
confidence: 94%
“…The PI3K/AKT pathway is important to and responsible for cell life cycle, proliferation, aging, survival, and apoptosis [ 41 ]. There are many literatures proposing that PI3K/AKT may be a target molecular signaling pathway in oncotherapy [ 42 44 ] which raises the importance of PI3K/AKT pathway. However, excessive activation of PI3K/AKT pathway may lead to neoplastic lesion [ 45 ]; appropriate activation is essential when this pathway is used in antiapoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The transfection process can be affected by many unknown factors. However, several studies have linked the transfection efficiency and cytotoxicity of PEI preparations to the physicochemical properties, the molecular weight and the branching ratio of polymer [41,42], the amount of DNA, the DNA ratio to the PEI, the timing and the solution conditions for complex formation, the transfection medium and cell density at time of transfer [43,44]. In addition, many factors, including temperature, surfactant, complex concentration, ionic strength, viscosity, pH, can significantly affect the aggregation process.…”
Section: Peimentioning
confidence: 99%